A 2.4 GHz sub 1-mW highly linear differential LNA using balun transformer gm-boosting technique. (January 2022) - Mazhabjafari, Babak; Shamsi, Hossein
Abstract: This paper presents a passive gm -boosting differential low noise amplifier (LNA) for low power applications using a single-to-double transformer. This LNA improves noise figure and linearity with no extra power penalty by using the front-end balun together with noise and distortion cancelation. To address the excess power and noise that are introduced by the auxiliary amplifier, both the current reuse and resistive feedback techniques are used. The input balun provides the differential signals from the single ended input signal and boosts the gm of the amplifier. gm -boosting together with the distortion reduction technique improve both the second and third order nonlinearity. The detailed analysis and simulations including Gain, NF, and Linearity in a standard 65nm CMOS technology are given. Simulation results reveal that the LNA achieves over 23.5 dB gain, 2.8 dB NF, IIP3 and IIP2 of +4.3 dBm and +46 dBm, respectively. It consumes 620 µW from a 0.8 V supply voltage while the total effective die area is 0.21mm 2 . Graphical abstract: Image 1